Using new tools to support creative community engagement with open educational resources. (12th October 2011) - Wilson, Tina; McAndrew, Patrick
The availability of community building tools and open educational resources (OER) affords the creation of new and innovative learning spaces. However in much of the work on OER the focus has been on providing content, rather than on how tools can be used in conjunction with available content to create a shared space that could improve the impact of such resources. A series of studies taking a subject point of view looked at the prospects for collaborative and cooperative working around OER from the perspectives of teachers and technical experts, considering in particular whether they would become involved in open environments. The studies discussed give an insight into how academics view social tools and techniques and whether they would use open arenas for formal and informal learning. The topic of OER and associated facilitative tools is important and this paper looks beyond content production issues to contribute to the debate on how collaborative and cooperative working can be established around OER.